Thermal conductivity of electrospun polyethylene nanofibers. Issue 40 (28th September 2015) - Ma, Jian; Zhang, Qian; Mayo, Anthony; Ni, Zhonghua; Yi, Hong; Chen, Yunfei; Mu, Richard; Bellan, Leon M.; Li, Deyu
Abstract : Combined structure (a) and property (b) characterization discloses how to fabricate electrospun nanofibers with enhanced thermal condcutivity. Abstract : We report on the structure-thermal transport property relation of individual polyethylene nanofibers fabricated by electrospinning with different deposition parameters. Measurement results show that the nanofiber thermal conductivity depends on the electric field used in the electrospinning process, with a general trend of higher thermal conductivity for fibers prepared with stronger electric field. Nanofibers produced at a 45 kV electrospinning voltage and a 150 mm needle-collector distance could have a thermal conductivity of up to 9.3 W m −1 K −1, over 20 times higher than the typical bulk value. Micro-Raman characterization suggests that the enhanced thermal conductivity is due to the highly oriented polymer chains and enhanced crystallinity in the electrospun nanofibers.